Behaviour of reinforced mortarless interlocking brick wall under cyclic loading. (15th May 2023) - Xie, Guanyu; Zhang, Xihong; Hao, Hong; Shi, Tingwei; Cui, Liuliang; Thomas, Joyis
Highlights: The studied interlocking brick wall exhibits a considerable deformation capacity. The wall strength keeps increasing after the formation of major diagonal cracks. The equivalent damping ratio decreases with the imposed displacement. DIC analysis reveals the subtle inter-brick movements. Abstract: Interlocking brick masonry has gained much attention due to its high construction efficiency and low labour skill requirement. Most designs of interlocking bricks only use interlocking keys to provide alignment for easy construction, and most previous studies of interlocking masonry structures concentrate on their static loading capacities. This study examines the behaviour of reinforced mortarless interlocking brick walls under cyclic loading. Interlocking brick wall made of a specific type of interlocking bricks with large keys that provide not only alignment in construction but also shear resistance is constructed and tested under in-plane cyclic loading. A detailed numerical model is generated and validated with the testing data, which is then used to assist the analysis of wall responses. The damage mode, hysteresis response and energy dissipation characteristics are analysed. The test results are compared with conventional masonry wall from literature to demonstrate the superior performance of interlocking masonry wall in resisting seismic loading and dissipating seismic energy. The influences of axial precompression and shear span-to-length ratio are investigated via numerical modelling.